Preventing Occupational Musculoskeletal Disorders: Effect of Stretching Exercise in Reducing Pain Among Factory Workers - Faizah Nurul Fitri; Dea Linia Romadhoni; Alinda Nur Ramadhani; Cahyo Setiawan (Indonesian Journal of Medicine, 2025)
Background: Musculoskeletal disorders (MSDs), often caused by prolonged static and repetitive sitting, can lead to pain and discomfort. Regular stretching every two hours may help alleviate this pain. This study aimed to evaluate the effectiveness of performing stretching exercises every two hours in reducing pain associated with the risk of MSDs. Subjects and Method: A quasi experimental study was carried out at Berdijaya Factory, Surakarta, Central Java, Indonesia. A total of 40 factory workers with MSDs complaint was recruited using a purposive sampling. The dependent variable was pain. The independent variable was stretching exercise every 2 hours per day for 2 weeks. Pain was measured using numeric rating scales (NRS). The data were tested before and after intervention using paired t test. Results: After two weeks of intervention, mean of pain score (Mean= 3.88; SD= 1.25) was lower than before (Mean= 5.08; SD= 1.09), with (p = 0.025). Conclusion: Stretching exercises performed every 2 hours per day for 2 weeks can reduce musculoskeletal pain among factory workers.